The contemporary Middle East foreign intervention and authoritarian governance since 1979 - Bunton, Martin P.; Robbins, Keith (Hoboken, NJ Wiley-Blackwell, 2024)
"This chapter explores the significance of the Cold War, both as a source of the conflicts which unfolded in the Middle East from 1979 to 1991 (and beyond) and as a legacy of mindsets and approaches (including the exercise of military power and the construction of exaggerated threats). Both the US and USSR saw the region's resources and strategic location as vital to securing their own national interests. Though rarely engaging in direct military action on the ground, during this period, they competed for influence among the regional powers. Viewing the region almost exclusively through the lens of the Cold War, superpower interventions often ignored the local roots of regional conflicts (thus exacerbating and prolonging them) or bolstered a geopolitical status quo that was centered more on their own interests than on the aspirations of the region's peoples. However, regional actors were not simply puppets, and attempts to assess the overall impact of the Cold War in the Middle East must also consider the extent to which local leaders could manipulate superpower rivalries, accepting foreign aid or arms for their own regional or domestic designs. Either way, not only did superpower rivalry contribute to persistent instability in the Middle East, but the legacy of Cold War interventions continued to influence the region's politics well after the collapse of the Soviet Union in 1991"--
Superpower Rivalry & the Shifting Terrains of War and Peace -- America's Unipolar Moment & 'the New Middle East' -- The Palestinian-Israeli Conflict and the US shaped Peace Process -- The Authoritarian Bargain, Religious Politics & the 2011 Arab Uprisings -- Multipolarity & Regional Rivalries.
Includes bibliographical references and index.
Keywords: Middle East -- Foreign relations -- 1979-.; Middle East -- Foreign relations -- United States; Middle East -- Politics and government -- 1979-.; United States -- Foreign relations -- Middle East